Ambulatory intravenous analgesia using elastomeric pumps in patients undergoing plastic surgery: prospective case series - Ramírez-Latorre, Juan Luis; Patiño-Arias, Andrés; López-Hernández, Carlos Andrés; Giraldo-Salazar, Olga; Yepes-Tejada, David Alonso; Erazo-Posada, Sandra Elena (Colombian Journal of Anesthesiology, 2018)
Introduction: Cosmetic plastic surgery interventions are usually associated with significant postoperative pain. As they are outpatient procedures, analgesic management is limited mostly to oral medication, resulting in suboptimal pain control, one of the most frequent complaints of patients undergoing these surgical procedures. Elastomeric pumps have been studied for continuous infusion of intravenous analgesics in other types of surgeries associated with significant pain. Objective: The main objective of this study was to evaluate postoperative pain control in adult patients who underwent mammoplasty, abdominoplasty, liposuction, or combined procedures using elastomeric pumps for postoperative analgesic management in continuous intravenous infusion. Materials and methods: A prospective sample of 100 patients who accepted postoperative pain management was collected. Satisfaction was evaluated using a survey, and pain control was assessed on postoperative days 1,3, and 5, and a determination of adverse reactions associated with analgesia using this device was also assessed. Results: Optimal pain control and a satisfaction greater than 90% were observed from the first postoperative day of the intervention. Conclusion: We recommend this analgesic strategy based on evidence of excellent postoperative ambulatory pain control.